Faktor-faktor yang mempengaruhi terjadinya free sex pada remaja : Literatur Review - Sutrisminah, Emi; Saskia, Firyal Sechan; Susiloningtyas, Is (Jurnal Kebidanan Malakbi, 2025)
"Free sex" generally refers to sexual activity occurring outside of a committed, exclusive relationship, often without the expectation of marriage. Adolescent sexuality is a multifaceted and intricate aspect of human development, laden with social and psychological complexities. Research within the Indonesian context reveals a concerning trend: a significant proportion of high school students initiate sexual activity during their formative years. This literature review delves into the multifaceted factors that shape adolescent sexual behavior, encompassing a range of influences such as religious beliefs, peer pressure, the quality of sex education received, and the pervasive impact of social media. A profound understanding of these intricate factors is paramount for the development of effective strategies that empower adolescents to make informed and responsible sexual decisions, ultimately fostering their healthy and holistic development. This study employed a Literature Review methodology, utilizing the PubMed and Google Scholar databases to identify relevant research articles. A total of 16 articles were initially retrieved, with 10 articles ultimately selected based on predefined criteria. The search focused on articles published between 2016 and 2023, prioritizing those available in full text, open access, and published in reputable scientific journals, both in English and Indonesian. A comprehensive review of the selected articles was then conducted, focusing on the specific research topic. The results showed that the factors that influence the occurrence of free sex in adolescents are: Religious Values (p value= 0.017, so p<0.05), the role of parents (p value= 0.002, so p<0.005), peers (p value = 0.005, then p<0.005), information media (p value= 0.003, then p<0.005), and socio-economics (p value= 0, then p<0,005). In conclusion, adolescent sexual activity is influenced by a complex interplay of factors, including religious values, parental guidance, peer influence, media exposure, and socioeconomic conditions. Addressing this issue requires a multifaceted approach that encompasses comprehensive sex education, strong family support, and efforts to mitigate the impact of socio-economic disparities.